Mestrado acadêmico e o desenvolvimento profissional de professores da Educação Básica: contribuições na formação, pesquisa e prática de egressos do PPGEd-So/UFSCar - Francisco, Aline Luz Mesquita (Universidade Federal de São Carlos, 2024)
This scientific production in the area of education addresses the aspect of teaching professional development related to the academic master's course in order to answer the following question: what are the contributions of the training experienced in the academic master’s degree in education at the Federal University of São Carlos on the Sorocaba/SP campus? for the professional development and educational practice of graduates in Basic Education? The aim, in general, is to investigate the contributions of the academic master’s degree in education at the Federal University of São Carlos in Sorocaba/SP in the professional development of Basic Education teachers from the perspective of PPGEd-So graduates. The qualitative and quantitative research used documental analysis of the pedagogical political project, curricular matrix and general and specific guidelines of the program involved to construct data; initial mixed electronic questionnaire with PPGEd-So graduates from 2013 to 2020; and semi-structured interview with a sample of questionnaire respondents with initial training in pedagogy or teaching degrees and working as Basic Education teachers. By providing comprehensive data on the master’s perception regarding their postgraduate career, the results reveal significant contributions to the professional development of teachers in the areas of training, research and practice, identifying limits and possibilities of the master's course in the academic modality in this process, locally and generally. In a complementary way, there were important benefits for the Postgraduate Program addressed (PPGEd-So) due to the systematic overview of its impact on the personal, academic and professional trajectory of graduates, also stimulating new investigations and in-depth studies that value the informative potential of graduates in the improvement of educational processes.

This scientific production in the area of education addresses the aspect of teaching professional development related to the academic master's course in order to answer the following question: what are the contributions of the training experienced in the academic master’s degree in education at the Federal University of São Carlos on the Sorocaba/SP campus? for the professional development and educational practice of graduates in Basic Education? The aim, in general, is to investigate the contributions of the academic master’s degree in education at the Federal University of São Carlos in Sorocaba/SP in the professional development of Basic Education teachers from the perspective of PPGEd-So graduates. The qualitative and quantitative research used documental analysis of the pedagogical political project, curricular matrix and general and specific guidelines of the program involved to construct data; initial mixed electronic questionnaire with PPGEd-So graduates from 2013 to 2020; and semi-structured interview with a sample of questionnaire respondents with initial training in pedagogy or teaching degrees and working as Basic Education teachers. By providing comprehensive data on the master’s perception regarding their postgraduate career, the results reveal significant contributions to the professional development of teachers in the areas of training, research and practice, identifying limits and possibilities of the master's course in the academic modality in this process, locally and generally. In a complementary way, there were important benefits for the Postgraduate Program addressed (PPGEd-So) due to the systematic overview of its impact on the personal, academic and professional trajectory of graduates, also stimulating new investigations and in-depth studies that value the informative potential of graduates in the improvement of educational processes.
Academic master's degree and the professional development of Basic Education teachers: contributions to the training, research and practice of PPGEd-So/UFSCar graduates
Keywords: Desenvolvimento Profissional; Mestrado Acadêmico; Formação de Professores; Saberes Docentes; Professional Development; Academic Master's Degree; Teacher Training; Teaching Knowledge; CIENCIAS HUMANAS::EDUCACAO